Working hours associated with unintentional sleep at work among airline pilots - Elaine Cristina Marqueze; Ana Carolina B Nicola; Dag Hammarskjoeld M D Diniz; Frida Marina Fischer
ABSTRACT OBJECTIVE Tto identify factors associated with unintentional sleep at work of airline pilots. METHODS This is a cross-sectional epidemiological study conducted with 1,235 Brazilian airline pilots, who work national or international flights. Data collection has been performed online. We carried out a bivariate and multiple logistic regression analysis, having as dependent variable unintentional sleep at work. The independent variables were related to biodemographic data, characteristics of the work, lifestyle, and aspects of sleep. RESULTS The prevalence of unintentional sleep while flying the airplane was 57.8%. The factors associated with unintentional sleep at work were: flying for more than 65 hours a month, frequent technical delays, greater need for recovery after work, work ability below optimal, insufficient sleep, and excessive sleepiness. CONCLUSIONS The occurrence of unintentional sleep at work of airline pilots is associated with factors related to the organization of the work and health.